A Review On Various Steps In Apple Fruit Grading - Kottath, Anu V (International Journal of Computer Sciences and Engineering, 2025)
Image processing is used to transform images into digital form and carry out some process on it, and get an improved image or obtain some useful details from it . Image processing has a lot of applications especially in agricultural, food industries, quality control and classification of products. Quality control in apple-based industries and marketing plays an important role in producing high quality products. Traditionally, apple quality inspection is performed by human experts. But the accuracy of them is low. To solve this there are different apple grading techniques and each techniques follow the same steps. Apple graded in three or more quality grades .These grades are AAA, AA and A; A, B, C. This review deals with compare different methods used in each step of apple grading and identify the best methods